Estudio de caso en la fase de operación de la planta de tratamiento de aguas residuales, en el cantón Salcedo, barrio Chipualo, provincia de Cotopaxi. - Caicedo Núñez, Daniel Eduardo (2020)
The present investigation outlined a solution proposal to this problem when implementing an aireación system in the tank of oxidation whose starting point is the results of the laboratory analyses. As it was mentioned previously, the problem that is given in the treatment plant is the exit of bad scents and some parameters that are not fulfilling the permissible limits. Therefore, when implementing the aeration system that is to inject compressed air he/she stays in constant movement the mixture and in turn it absorbs I oxygenate that it is necessary for purification of the water, reducing this way the biochemical demand of oxygen (DBO5), it demands oxygen chemistry (DQO), fecal coliforms, nitrogen ammoniac, parameters that were obtained outside of the ranges. By means of the obtained results of the physical-chemical analyses, an increment of demand biochemistry of oxygen of 231.9 mg/l is observed, being the limits permissible 100 mg/l, the one is do of the chemical demand of oxygen it is of 364 mg/l, being the limits permissible 200 mg/l, the fecal coliforms is on the -2420 NMP/100ml, being the permissible limits 2000 NMP/100ml, the nitrogen ammoniac this envelope the 31,00 mg/l, being the limits permissible 30,00 mg/l, for what intends to implement an aireación system whose purpose is that the parameters already mentioned they fulfill the permissible limits and decrease the emanation of scents.